2021
DOI: 10.3892/ol.2021.12963
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tumor‑associated MUC1 and its glycans expressed in mucoepidermoid carcinoma

Abstract: Mucoepidermoid carcinoma (MEC) is one of the most frequently misdiagnosed tumors. Glycans are modulated by malignant transformation. Mucin 1 (MUC1) is a mucin whose expression is upregulated in various tumors, including MEC, and it has previously been investigated as a diagnostic and prognostic tumor marker. The present study aimed to reveal the differences in the mucin glycans between MEC and normal salivary glands (NSGs) to discover novel diagnostic markers. Soluble fractions of salivary gland homogenate pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
3
0
1
Order By: Relevance
“…1C). Mucins in all patients (1-3) with MEC and three patients (7,9,10) with NSGs were stained with AAL (Fig. 1D).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…1C). Mucins in all patients (1-3) with MEC and three patients (7,9,10) with NSGs were stained with AAL (Fig. 1D).…”
Section: Resultsmentioning
confidence: 93%
“…Previously, we found that MEC produced MUC1 distinctively modified by sialylated core-2 O -glycans (GlcNAcβ1-6(Galβ1-3)GalNAcαSer/Thr) 10 . However, it remains unclear which cells in MEC tissues produce such characteristic modified MUC1.…”
Section: Introductionmentioning
confidence: 99%
“…Las investigaciones sobre la expresión de las mucinas, especialmente MUC-1, en distintos tipos de cánceres son numerosas 10 . Sin embargo, los trabajos sobre los tumores de las glándulas salivales son escasos, relacionados principalmente con el adenoma pleomórfico y el carcinoma mucoepidermoide 10,[12][13]17,[36][37] . La expresión de las mucinas unidas a membrana (MUC-1 y MUC-4) y las mucinas secretorias (MUC-2, MUC-5AC, MUC-5B, MUC-6, and MUC-7) fueron estudiadas en 40 carcinomas mucoepidermoides por Alos et al 12 .…”
Section: Discussionunclassified
“…Previously, we found that MEC produced MUC1 distinctively modi ed by sialylated core-2 O-glycans (GlcNAcβ1-6(Galβ1-3)GalNAcαSer/Thr) 10 . However, it remains unclear which cells in MEC tissues produce such characteristic modi ed MUC1.…”
Section: Introductionmentioning
confidence: 99%